Analisis Starategi Pengelolaan Dana dalam Penyelenggaraan Program Pendidikan Non-Formal pada Pusat Kegiatan Belajar Masyarakat di Kabupaten Ogan Ilir - Nopiati, Erti (Yayasan Sembilan Pemuda Indonesia, 2021)
The purpose of this study is to examine the PKBM Institution Management strategy in the Ogan Ilir Regency's execution of equality education programs. In this study, the case study method with a qualitative approach was applied. The data source for this study is the district's PKBM manager, as well as the head of PNF-Dikmas. Data collection techniques using interview guidelines, observation, and documentation. The interactive analysis model which includes data collection, data reduction, data presentation, and verification or conclusion is the assessment data analysis used. The data validity technique is using source triangulation. The conclusions obtained from this study are the fund management strategy in the implementation of the Non-Formal Education Program carried out by PKBM in Ogan Ilir Regency using a public education strategy, competency strategy to government agencies, both central and local governments. relevant to the main task of administering Non-Formal Education.